Analgesic, Anti-Inflammatory, and Chondroprotective Activities of Cryptolepis buchanani Extract: In Vitro and in Vivo Studies - Nutthiya Hanprasertpong (2018)
© 2014 Nutthiya Hanprasertpong et al. Cryptolepis buchanani Roem. & Schult. is widely used in folk medicine in Southeast Asia for treating muscle tension and arthritis. This study aimed to investigate an analgesic activity of the methanol extract of C. buchanani (CBE) in acetic acid-induced writhing response in mice, and to examine its anti-inflammatory activity in ethyl phenylpropiolate- (EPP-) induced ear edema and carrageenan-induced paw edema in rats. Its effects on cartilage degradation induced by interleukin-1β (IL-1β) in porcine cartilage explant culture were also determined. This study demonstrated that CBE significantly reduced acetic acid-induced writhing response. It also inhibited edema formation in both EPP-induced ear edema and carrageenan-induced paw edema models. In cartilage explant culture, CBE significantly reduced the sulfated glycosaminoglycan and hyaluronan released into culture media while it reserved the uronic acid and collagen within the cartilage tissues. It also suppressed the matrix metalloproteinase-2 activity with no effect on cell viability. In conclusion, CBE shows analgesic, anti-inflammatory, and chondroprotective effects in this preliminary study. Therefore, CBE may be useful as an alternative treatment for osteoarthritis.